Produksi Ruang Terbuka Hijau Publik Taman Terpadu dan Respon Warga di Taman Kelurahan Pondok Jaya, Kota Depok - Lintang Yuniar Pratiwi; Agus Dharma Tohjiwa; Irina Mildawani (http://arl.faperta.ipb.ac.id/, 2020)
Horizontal Urban Expansions Model significantly contributes to land transformation and affects multiple problems including environtmental damage. Ideally it must be balanced by Urban Green Space supply for sustainability and liveabilty of a City. Society aspect become apart of sustainability’s domain and human factors will be considered through perception. In order to implement as mandatory of Law of Republic of Indonesia no 26/2007 Concerning Spatial Management, local government needs to basically establish local regulation on how to carry it out. The Depok City Government Public Space Regulation has already been arranged through Depok City’s Mission (2016-2021) which Increase the quality of the public services, and building infrastructure and open space including Mayor’s Promise to build urban park in 63 of Depok’s urban village. Since it was on first year, there were disagreement where the inhabitants refused park development around them. This study wants to find out the factors influencing inhabitant’s response to Pondok Jaya Urban Village Park Development. The research is using qualitative method with Case Study and an in-depth interview, analyzing qualitative data by open coding, axial coding and selective coding analysis. The research’s result revealed three category of inhabitant’s response who has different causal factors, they are Strongly Agree (precedent, physical & social benefit), Somewhat Agree (priviledges, maintenance & concept planning) and Strongly Disagree (Intervnetion, Development Process, Existing Condition & authority-function changes). This study may gain knowledge and understanding the way to better formulation of next Depok’s public green space regulation.